2006
DOI: 10.1161/01.hyp.0000205150.43169.2c
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Intake of North American Ginseng Has No Effect on 24-Hour Blood Pressure and Renal Function

Abstract: Abstract-Ginseng is consumed by 10% to 20% of adults in Asia and by up to 5% in Western countries. Despite observational evidence suggesting a link between its intake and the development of hypertension, there remains no long-term scrutiny for its effect on blood pressure (BP). We therefore undertook a randomized, placebo-controlled, double-blinded, crossover trial in 52 hypertensive individuals to determine the effect of 12-week North American ginseng intake on 24-hour BP; we also measured serum cystatin C as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 37 publications
(53 reference statements)
1
39
0
1
Order By: Relevance
“…1). The key data are summarized in Table 1 [7,[14][15][16][17]. Two RCTs [7,14] tested North American ginseng (NAG, Panax quinquefolius), and the other three RCTs [15][16][17] assessed Korean ginseng or Korean red ginseng (KRG, Panax ginseng).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). The key data are summarized in Table 1 [7,[14][15][16][17]. Two RCTs [7,14] tested North American ginseng (NAG, Panax quinquefolius), and the other three RCTs [15][16][17] assessed Korean ginseng or Korean red ginseng (KRG, Panax ginseng).…”
Section: Resultsmentioning
confidence: 99%
“…The key data are summarized in Table 1 [7,[14][15][16][17]. Two RCTs [7,14] tested North American ginseng (NAG, Panax quinquefolius), and the other three RCTs [15][16][17] assessed Korean ginseng or Korean red ginseng (KRG, Panax ginseng). Four of the included trials used a two-armed cross-over double-blind design [7,[14][15][16], while one RCT employed a parallel open design [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Associated adverse effects include nausea, diarrhea, euphoria, insomnia, headaches, hypertension, hypotension, mastalgia, and vaginal bleeding (83,84). For example, Panax ginseng may interact with caffeine to cause hypertension, and it may lower blood alcohol concentrations (85). It may also decrease the effectiveness of warfarin (Coumadin) (86).…”
Section: Adverse Effects Drug Interactions and Contraindicationsmentioning
confidence: 99%
“…In a separate study [15], one-time treatment with KRG (50 mg/kg) decreased the mean BP and heart rate in 12 healthy, non-smoking male volunteers [15]. In contrast, other studies have shown no effect of ginseng on BP [16][17][18], as neither long-term (12 weeks) [16] nor one-time treatment [17] with North American ginseng significantly changed the BP in patients with hypertension. These discrepant reports may be attributable to the heterogeneity of ginsenoside preparations or differences among the study subjects.…”
Section: Discussionmentioning
confidence: 89%